The formation of geyser eggs at Old Faithful Geyser, Yellowstone National Park, U.S.A. (September 2018) - Smith, Isaac J.; Lynne, Bridget Y.; Jaworowski, Cheryl; Qasim, Ilyas; Heasler, Henry; Foley, Duncan
Highlights: The first published geyser egg study from Old Faithful Geyser. This study documents the mineralogy and architecture of a rare geyser egg. A unique combination of analytical techniques including SEM, EDS, XRF, XRD, iTRAX and CT scanning. Abstract: One geyser egg (a smooth, oval, siliceous pebble found in alkali chloride hot pools) from the siliceous sinter slope surrounding Old Faithful Geyser was examined to determine its genesis, sinter architecture and elemental composition. The multi-technique approach included Scanning Electron Microscopy (SEM), petrographic microscopy, X-Ray Diffraction, Energy Dispersive Spectroscopy, iTRAX Core Scanner and Computerised Tomography (CT) scans. The geyser egg architecture consists of alternating smooth and porous concentric bands of opal-A silica around a nucleus. These alternating bands are signatures of changes in the degree of silica oversaturation of the discharging fluid. CT scans mapped changes in density throughout the sample and also showed concentric banding of varying density around a core. SEM observations showed the geyser egg has an abiotic origin with subsequent microbial filamentous void infill creating an abiotic-biotic sinter structure. iTRAX scans revealed the geyser egg preserved signatures of changes in fluid chemistry with time, and that the core is rich in arsenic and calcium. iTRAX scans also documented significantly higher concentrations of gallium in the geyser egg compared to those documented in rhyolites and tuffs from the same area. Unravelling geyser egg formation mechanisms and their microbial content provide useful insights on fluid chemistry, water temperature, and flow conditions in these unique hot spring environments.